(untitled) (Journal of Nursing Education in Psychiatric and Mental Wellbeing, 2026)
Background: Adverse Childhood Experiences (ACEs) are well-established determinants of long-term physical, psychological, and behavioral health outcomes. Exposure to childhood adversity disrupts neurobiological development, stress regulation, and coping mechanisms, increasing vulnerability to mental disorders, chronic diseases, and maladaptive behaviors, including emerging behavioral addictions such as smartphone and internet addiction. Given the high prevalence of ACEs globally, there is an urgent need for scalable and accessible interventions that support early identification, prevention, and resilience-building. Objective: This review aims to synthesize existing evidence on the impact of ACEs on health outcomes across the life course and to examine the role of digital health interventions in screening, prevention, intervention, and resilience-building among individuals exposed to childhood trauma. Methods: A narrative literature review was conducted focusing on peer-reviewed studies published in English over the past ten years. Included studies examined ACE-related physical, psychological, or behavioral outcomes and the application of digital health technologies such as mobile health (mHealth), telehealth, artificial intelligence, e-therapy, and wearable devices in addressing ACE-related risks. Results: The reviewed evidence demonstrates a strong dose–response relationship between ACE exposure and adverse mental, physical, and behavioral health outcomes. Digital health interventions show growing potential in early screening, trauma-informed care delivery, and resilience enhancement. Interventions incorporating telemedicine, mHealth platforms, and digital resilience training were associated with improvements in mental health symptoms, coping skills, and accessibility of care, although study quality varied. Conclusion: Digital health technologies represent a promising, scalable approach to mitigating the long-term consequences of ACEs. Integrating trauma-informed principles into digital platforms may enhance prevention, intervention, and resilience-building efforts, supporting improved public health outcomes across vulnerable populations.